Rethinking Christian Spirituality. Exploring Challenges and Opportunities Beyond the Global North-South Binary - Petrus Simarmata; Milda Longgeita Pinem; Armada Riyanto (Bogoslovska Smotra)
This article examines Christian spirituality in a global context, moving beyond the typical North-South binary. Informed by a comprehensive literature review, the study offers an in-depth examination of the domain, addressing key issues such as the commercialization, individualization, and secularization of spirituality. It delves into the transformative potential that lies in embracing global interconnectedness, alongside the significant influences of the post-Vatican II era, and the vibrant and critical perspectives brought forth by the younger generation. These elements are pivotal in redefining and shaping the contemporary spiritual landscape. Proposing a synthesized spiritual landscape that champions a more inclusive spirituality, open to dialogue and prioritizing solidarity, the article underscores the necessity for an evolved Christian spirituality in tune with the varied and interconnected global context of today. It advocates for enhanced adaptability and a stronger sense of unity among Christian communities worldwide, aiming to more effectively navigate and leverage present challenges and opportunities, thereby fostering a more robust and responsive spiritual practice.